(untitled) (Global Journal of Management and Business Research, 2019)
Due to the ignorance about the contribution that this billing system offers in the tax collection, the present investigation analyzed the incidence of the electronic invoicing in the tax collection in the payment of the taxpayers of the Canton Latacunga. The investigative approach used in this work was quantitative, descriptive, explanatory and deductive. Information was collected in the Internal Revenue Service (SRI), specifically of the tax obligations Withholding Tax, Income Tax, Value Added Tax and Special Consumption Tax. This investigation verified the percentage increases of customers incorporated into the electronic invoicing regime, economic amounts collected before and after the implementation of this billing system and its variations and differences. The vital performance and efficiency of the management of electronic invoicing in tax collection and tax obligations carried out by taxpayers. Based on the results obtained, it is essential that the SRI encourages customers to use this system, encouraging, innovation, efficiency and the competitiveness in commercial operations carried out by users must be achieved in order to achieve greater collections for the Treasury and control them timely.